2020
DOI: 10.2139/ssrn.3539236
|View full text |Cite
|
Sign up to set email alerts
|

Global Macro-Financial Cycles and Spillovers

Abstract: We develop a new dynamic factor model that allows us to jointly characterize global macroeconomic and financial cycles and the spillovers between them. The model decomposes macroeconomic cycles into the part driven by global and country-specific macro factors and the part driven by spillovers from financial variables. We consider cycles in macroeconomic aggregates (output, consumption, and investment) and financial variables (equity and house prices, and interest rates). We find that the global macro factor pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…This implies that there exist a global cycle in credit that accounts for about one-third of variation in the credit growth on average for the sample of 17 countries. This is comparable to the results found by Hirata et al (2012); but significantly larger than that found by Ha et al (2017) who only find 2 to 4 percent contribution of the global factor. The remaining variance is attributable to idiosyncratic components, which could include regional, country-specific or variable-specific components.…”
Section: Variance Decompositionsupporting
confidence: 83%
See 2 more Smart Citations
“…This implies that there exist a global cycle in credit that accounts for about one-third of variation in the credit growth on average for the sample of 17 countries. This is comparable to the results found by Hirata et al (2012); but significantly larger than that found by Ha et al (2017) who only find 2 to 4 percent contribution of the global factor. The remaining variance is attributable to idiosyncratic components, which could include regional, country-specific or variable-specific components.…”
Section: Variance Decompositionsupporting
confidence: 83%
“…Only Portugal has less than 20 percent variation in equity-price growth attributable to the global factor. The average share of variance attributable to the global equity-price factor that I find is smaller than the studies that use constant parameter models (Ha et al (2017); Hirata et al (2012); ) who account for about 60 percent variation attributable to the global factor. Miranda-Agrippino and Rey (2015) find that 66 percent of the variation in returns of risky assets is attributable to the global factor.…”
Section: Variance Decompositioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Long historical comparisons based on quarterly data are almost exclusively focused on G7 countries(Kose, Otrok and Whiteman (2008),Doyle and Faust (2005),Ha et al (2017)). Studies with a broader geographical focus are constrained to the post 90's because of data constraints in EMs and smaller advanced economies (e.g.…”
mentioning
confidence: 99%
“…International spillovers appear to be quantitatively pronounced, and the strength and direction of spillover effects are found to evolve heterogeneously across G7 countries. Ha et al (2020) apply a dynamic factor model to G7 countries to jointly characterize global macroeconomic and financial cycles and the spillovers between them. The paper distinguishes between global, variable and country specific factors of macroeconomic aggregates and financial variables.…”
Section: Economic Cycles -Macro-financial Linkagesmentioning
confidence: 99%